2015
DOI: 10.1538/expanim.15-0004
|View full text |Cite
|
Sign up to set email alerts
|

Novel phenotype in beagle dogs characterized by skin response to compound 48/80 focusing on skin mast cell degranulation

Abstract: Beagle dogs have long been employed in toxicology studies and as skin disease models. Compared with other experimental animal species, they are known to be susceptible to skin responses, such as rashes, from exposure to various chemical compounds. Here, a unique dog phenotype was identified that showed no skin response to compound 48/80, a mast cell degranulating agent. Although the skin responses to intradermal injection of polyoxyethylene castor oil derivative (HCO-60, a nonionic detergent), histamine dihydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…29,30 It has been reported that in a unique nonresponsive phenotype of compound 48/80 in beagle dogs, compound 48/80 did not induce anaphylactoid skin reaction as per IDT, while HCO-60 did. 31 The significant difference in IDT score and percentage of mast cell degranulation within the dog groups in the present study indicate there is the possibility that individual differences in the response of HCO-ethoxylate could be present. Individual differences might be one reason why we experienced the uncommon anaphylactoid reaction to an ear drop.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…29,30 It has been reported that in a unique nonresponsive phenotype of compound 48/80 in beagle dogs, compound 48/80 did not induce anaphylactoid skin reaction as per IDT, while HCO-60 did. 31 The significant difference in IDT score and percentage of mast cell degranulation within the dog groups in the present study indicate there is the possibility that individual differences in the response of HCO-ethoxylate could be present. Individual differences might be one reason why we experienced the uncommon anaphylactoid reaction to an ear drop.…”
Section: Discussionmentioning
confidence: 49%
“…Compound 48/80 is a potent chemical inducer of mast cell degranulation, and it has been shown to relay the signalling leading to mast cell degranulation via binding to mas‐related G protein‐coupled‐receptor X2 (MRGPRX2) in humans or MRGPRB2 in mice 29,30 . It has been reported that in a unique nonresponsive phenotype of compound 48/80 in beagle dogs, compound 48/80 did not induce anaphylactoid skin reaction as per IDT, while HCO‐60 did 31 . The significant difference in IDT score and percentage of mast cell degranulation within the dog groups in the present study indicate there is the possibility that individual differences in the response of HCO‐ethoxylate could be present.…”
Section: Discussionmentioning
confidence: 99%
“…Our effort found 19,856 protein coding and 4,724 non-protein coding genes in beagle dogs ( Table 2 ). This work was conducted in the dog strain (Beagle) used for drug safety toxicology studies ( Weber et al, 2011 ; Uchida et al, 2015 ). At the time of this publication, the only dog related RNAseq databases that exist are focused on tumor tissue.…”
Section: Discussionmentioning
confidence: 99%